2011
DOI: 10.1016/j.jvs.2010.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid management of proximal right subclavian artery aneurysms

Abstract: Surgical repair of proximal right subclavian artery aneurysms can be difficult. They typically require a combined mediastinal exposure to control the innominate and right common carotid arteries and a supra- or infraclavicular exposure for distal control, with either a segmental resection and bypass or a bifurcated reconstruction. In this report, we present four cases utilizing a single-stage, hybrid technique combining an endovascular stent graft and an extra-anatomical bypass to repair proximal right subclav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…[20][21][22][23][24][25] In a recent systematic review collecting overall 31 endovascular or hybrid published cases for aneurysms on aberrant subclavian arteries, Yang et al 1 found that the hybrid approach, including thoracic stent grafting with distal subclavian ligation, was the most frequently used.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25] In a recent systematic review collecting overall 31 endovascular or hybrid published cases for aneurysms on aberrant subclavian arteries, Yang et al 1 found that the hybrid approach, including thoracic stent grafting with distal subclavian ligation, was the most frequently used.…”
Section: Discussionmentioning
confidence: 99%
“…Stent insertion alone is sometimes inadequate to treat the injury, and combinations of stenting with coils 15) , open surgery 16) or balloon occlusion 14) have been reported. One limitation of endovascular treatment in this case was that although the membrane of the covered stent was made using ePTFE, which is commonly used for artificial blood vessels, long-term patency has not been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin and clopidogrel were administered as antiplatelet therapy. Computed tomography on day 16 showed that the stent graft was in a suitable position, and the aneurysm had disappeared (Fig. 5 ).…”
Section: Case Reportmentioning
confidence: 99%
“…The approach to both open and endovascular SAA repair depends greatly on the anatomic location and involvement of the cerebrovascular circulation [8]. Anticipation of posterior circulation adequacy post-intervention is paramount to good outcomes and may have direct implications on the revascularization strategy employed [8,9]. Because of the dominance of the contra lateral vertebral artery, this patient's right vertebral was ligated without revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Open repair for aneurysms with intra-thoracic involvement frequently requires sternotomy or lateral thoracotomy [3], and hybrid techniques can often decrease the extent of exposure required for repair 9 . Although excellent long-term patency of direct arterial reconstruction of subclavian aneurysms has been reported, the resultant peri-operative morbidity can be prohibitive for selected patients [12].…”
Section: Discussionmentioning
confidence: 99%